1976
DOI: 10.1213/00000539-197611000-00016
|View full text |Cite
|
Sign up to set email alerts
|

The Anesthetic Potency of Lidocaine in the Rat

Abstract: The anesthetic effect of lidocaine was evaluated in rats by determining the change in anesthetic requirement of cyclopropane MAC that was produced by blood concentrations of lidocaine in the clinically useful range. A linear reduction in anesthetic requirement was produced with concentrations up to 1 mug/ml. Further increases in lidocaine up to 5.5 mug/ml resulted in no further decrease in cyclopropane requirement. Lidocaine was found to contribute a maximum MAC fraction of 0.4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1

Year Published

1981
1981
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 0 publications
2
19
1
Order By: Relevance
“…Volatile anesthetics have been suggested to produce a part of anesthesia immobility by inhibiting Na ϩ channels, because systemic injection of local anesthetics, which predominantly reduce Na ϩ channel functions, decreases MAC values in animals (DiFazio et al, 1976;Doherty and Frazier, 1998). More recently, Hodgson et al (1999) showed that lidocaine epidural anesthesia reduced the MAC value of sevoflurane from 1.18 to 0.52% (Hodgson et al, 1999).…”
Section: Figmentioning
confidence: 99%
“…Volatile anesthetics have been suggested to produce a part of anesthesia immobility by inhibiting Na ϩ channels, because systemic injection of local anesthetics, which predominantly reduce Na ϩ channel functions, decreases MAC values in animals (DiFazio et al, 1976;Doherty and Frazier, 1998). More recently, Hodgson et al (1999) showed that lidocaine epidural anesthesia reduced the MAC value of sevoflurane from 1.18 to 0.52% (Hodgson et al, 1999).…”
Section: Figmentioning
confidence: 99%
“…In humans, MAC decreases approximately 40% [determined as the effect in the presence of 70% nitrous oxide plus morphine premedication (1)]; in dogs the decrease is 37% (2) to 43% (3); in cats, 52% (4); in ponies by up to 70%, (5) and in rats, 50% (6). A maximum decrease of approximately 40%-50% appears to result, at least for some anesthetics and animals (1,6), a value similar to the 50%-60% maximum decrease produced by the blockade of N-methyl-d-aspartate (NMDA) receptors by dizocilpine (MK-801) (7). Is the mechanism underlying the decrease in MAC the same for MK-801 and lidocaine, i.e., blockade of transmission via NMDA receptors?…”
mentioning
confidence: 99%
“…We therefore suggest that inhibitory actions of local anesthetics on I h in thalamocortical cells and cortical or hippocampal pyramidal neurons may contribute to their central anesthetic-sparing actions. In addition, because inhibition of HCN channels in sensory neurons can reduce pain sensation (Chaplan et al, 2003), it is possible that anesthetic sparing (DiFazio et al, 1976;Himes et al, 1977;Senturk et al, 2002) or analgesic actions in postoperative or neuropathic contexts (Kingery, 1997;Smith et al, 2004) could be due to effects of systemic local anesthetics on HCN1 or HCN2 subunits expressed in nociceptors (Chaplan et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Lidocaine is the most important class 1B antiarrhythmic drug; it is used intravenously for the treatment of ventricular arrhythmias (Trujillo and Nolan, 2000;Pinter and Dorian, 2001). Lidocaine reduces minimal alveolar concentration of volatile anesthetics for the suppression of responses to painful stimuli in animals by 20 to 40% (DiFazio et al, 1976;Himes et al, 1977;Smith et al, 2004) and decreases the requirement of intravenous anesthetic propofol (Senturk et al, 2002). The local anesthetic lidocaine can produce ϳ0.4 minimal alveolar concentration (low-dose systemic application) (DiFazio et al, 1976) and decrease the bispectral index to 0 (higher-dose systemic application) (Gaughen and Durieux, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation